Film light : meaning and emotion - Thompson, Lara (Manchester : Manchester University Press, 2015)
Introduction Part I: The presence of light 1. Identity 2. Authenticity 3. The imaginary Part II: The absence of light 4. Mystery 5. The past 6. The magic hour Afterglow Index
boek